Construction of action in the structure of punggawa-sawi relationship in Burung Loe Island, Indonesia - Arifin, Ansar; Ansar, Cindy Israeni; Arsat, Muhamad; Garantjang, Muhammad Fauzan; Hamzah, Amiruddin (Department of Anthropology, Faculty of Social and Political Sciences, Hasanuddin University., 2023)
he construction of performance in the patron-client structure that functions as a socio-cultural agent in the management system and the utilization of fisheries resources is inseparable from the norm system practices carried out repeatedly in fisher groups. The study uses a qualitative approach to identify the construction process of performance through the practice of norms, ideas, and arenas of fisher's struggle (courtier). The study was conducted in Burung Loe Island, Sinjai Regency. Data obtained through observation, in-depth interviews, and focus group discussions (FGD) with large punggawa (ship owner), small punggawa (fisheries operational leader) and the crew. The results show that the social practices of electric fishers (pa'bagang rambo), tuna-mackerel fishers (pa'tongkol) and cages/aqua culture (keramba or fish farming) did not just happen, but were conditioned by nature and market logic would build them to choose the appropriate job. Fishers are bound by schemes of perception and thought that seem to be a collective phenomenon in the form of rituals and safety norms so that they are safe, calm, and get abundant wealth. The arena of fisher actualization is conditioned by the social structure of the punggawa who creates a patron-client dichotomy.